Design and Development of Android-Based “Tracked” Person Shooter Game Models - Ronaldi Subastian; Widuri Hesterananda (Journal of Multimedia Trend and Technology, 2023)
Games or games on the computer are visualizations that can provide a response back when given certain commands. First-Person Shooter, is a popular game because it uses a first-person perspective where the player becomes the main character in the game. Games are now entering the era of mobile games. Mobile Games Developer First Person Shooter made in Indonesia is still very rare, but this game can be played anywhere and is one of the most popular types of games. Then came the idea to make a Mobile version of the First Person Shooter game in worm research with Multimedia Development Life Cycle research. This game has been tested on 10 respondents with a questionnaire and the results are average above 50% of all assessment scores. The conclusion is that the Mobile version of the First Person Shooter Game has been successfully made and this game is feasible to be implemented on Android devices as well as as a medium of entertainment. Apart from that, this person shooter game model is very possible to be developed towards business processes as currently running.